(untitled) (Oratio Directa, 2022)
This study examines signs in The Official FIFA World Cup Qatar 2022 Theme video published on FIFA's official YouTube channel. A descriptive qualitative approach is applied through Roland Barthes's concepts of denotation, connotation, and myth, complemented by Susanne Langer's theory of symbols. The video runs for 1 minute 52 seconds, but the source notes that the sequence from 0:00 to 1:07 is repeated from 1:08 to 1:52; therefore, the analysis focuses on thirteen scenes in the first sequence. The denotative layer includes a white fabric, a maroon background, the tournament emblem, children playing football, simple goalposts, stadiums, a mosque, spectators, national flags, and the World Cup trophy. At the connotative layer, the source reads these elements as encounters between Qatari tradition and sporting modernity, simplicity and spectacle, as well as cultural particularity and global participation. The dominant myth constructed by the analysis is universal brotherhood: differences in nation, religion, culture, age, and social position are symbolically gathered within shared sporting joy. These meanings remain the researcher's interpretation of an audiovisual text rather than evidence of audience reception or FIFA's production intent.